Large-Scale RDA Enrichment of Legacy Data at the University of Houston System Libraries. Issue 3 (2nd April 2016) - Wu, Annie; Guajardo, Richard; Rodriguez, Stephanie
ABSTRACT: University of Houston (UH) Libraries, along with three other UH Systems libraries, took the initiative to implement Resource Description and Access (RDA), the new resource description standard, across their shared library database. An RDA Implementation Task Force was established to develop a plan and a strategy for the implementation process. The task force targeted a major goal of retrospective enrichment of all existing bibliographic records with RDA elements. This article discusses the RDA implementation planning, systems configuration, vendor collaboration, local RDA guidelines, training, and communication. Authors also identify challenges, benefits, and lessons learned from this process.